Real Estate Finance and Investments - Brueggeman, William B. (McGraw-Hill/Irwin, 2005)
Never HIGHLIGHT a Book Again! Virtually all testable terms, concepts, persons, places, and events are included.look no further for study resources or reference material. Cram101 Textbook Outlines gives all of the outlines, highlights, notes, and practice-tests for your textbook. Only Cram101 is Textbook Specific. Cram101 is NOT the Textbook.